STRATEGIES OF EFL UNDERGRADUATE STUDENTS AS GENERATION Z IN ACADEMIC WRITING DURING THE PANDEMIC - Fitri Palupi Kusumawati; Syaifudin Latif Darmawan; Refa'i Refa'i; Zenal Akbar (Universitas Muhammadiyah Metro, 2022)
The spread of Covid 19 has changed the educational learning system and learning strategies. The use of unlimited charge of internet, easiness of access, and the online classroom situation might change the students’ strategies in learning. Thus, this study aimed to investigate types of writing strategies and factors underlying the strategies preferences by EFL as Z generations Muhammadiyah University of Metro Academic year 2022/2023. The researcher conducted a descriptive qualitative study. The data were collected through 47 items of 5-Likert questionnaire and interview. The questionnaire consists of six strategies such as memory, metacognitive, compensation, cognitive, affective, and social. In regards to the first research question, the result revealed that the participants were medium strategy users with affective strategies to be the most dominant Nstrategies used. Then, followed by metacognitive, compensation, memory, and social strategies with cognitive to be the least strategies used. To respond objectives related to the internal and external factors underlying the participants’ preferences in selecting the strategies they chose, the researcher found internal factors consisting of self-motivation, self-confidence, lack of knowledge and feeling of under pressure. While external factors including the teacher's teaching style, classroom atmosphere, materials, and writing aspects.